Efficacy of Ultrasound for Sonologists, Sonographers and Nurses to assess high-risk conditions at Labor Triage in Pakistan : Efficacy of Ultrasound to assess high-risk conditions at Labor Triage - Sabir, Muhammad; Aster, Raheela; Rafiq, Rizwana; Raza, Muhammad Ahmad; Alam, Muhammad Asad; Alloudin, Aftab (Pakistan Journal of Health Sciences, 2023)
Healthcare problems that impede the effective delivery of health services, resulting in unequal access to care and suboptimal health outcomes, plague many countries. The absence of an expert medical personnel and diagnostic facilities are main causes of these problems. The worldwide ultrasound industry is still mainly unregulated, and national training policies and regulations that guarantee a minimal level of proficiency for safe practice differ. Requirements for reform and control of ultrasound usage have arisen since health professionals in many countries may perform ultrasounds with little to no training and without official certification. For this literature review, data from numerous search engines were obtained. The data for this study came from PubMed, Science Direct, NCBI, Medline, Medscape, and Google Scholar. It is a highly plausible alternative to teach nurses to do routine targeted obstetric scanning for the detection of high-risk pregnancies in order to make up for the lack of sonographers and sonologists in low-income countries. Therefore, sonologists are more effective than nurses in using ultrasonography to evaluate high-risk problems during labor triage.